Eating behaviour and lifestyle among School of Health Sciences students of Universiti Sains Malaysia - Ibrahim, Zalila (2013)
Eating habits and lifestyle factors are among the main determinants of body weight status. Students are among people that having problem in healthy eating habits and lifestyles. The purpose of this study were to determine the relationship between parents' income, eating habits, lifestyle factors and body weight status among School of Health Sciences students of USM. This study used cross sectional and quantitative design using random stratified sampling method. A total of 204 respondents were involved in this study. The questionnaire which adapted from Ayranci et al. 2010 including items related to sociodemographic characteristics, eating habits and lifestyle factors. The data were evaluated using percentage ratios, correlation tests and one-way ANOV A test. SPSS version 20.0 was used and results were considered significant at p < 0.05. Students of normal weight were 71.1 %, 13.7% were underweight while 15.2% were overweight. Percentage of students who had good eating habits was 83.3% while lifestyle was moderately scored (43.3%). Significant correlation was found between eating habits and body weight status using Pearson correlation (p = 0.004). Correlation between lifestyle factors and body weight status was also significant using Pearson correlation (p < 0.001 ). There was a significant mean difference between parents' income and body weight status (p = 0.003). This study suggests that health care providers should take a prevention step to improve the awareness of the students regarding knowledge for healthy eating habits and lifestyles.